2021
DOI: 10.1016/j.acap.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Modalities to Teach Evidence Based Medicine to Pediatric Clerkship Students: A Randomized Controlled Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…2 . Four studies had a low risk of bias [ 24 , 26 , 39 , 46 ], ten studies [ 23 , 29 , 31 , 34 , 35 , 37 , 44 , 47 , 51 , 53 ] had a high risk of bias and seven studies [ 41 43 , 45 , 49 , 50 , 52 ] had uncertain risk of bias as there was a lack of detail in the study methodology to genuinely judge the quality of the study. Table 3 provides further details about the evidence to support judgements about risk of bias for all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 . Four studies had a low risk of bias [ 24 , 26 , 39 , 46 ], ten studies [ 23 , 29 , 31 , 34 , 35 , 37 , 44 , 47 , 51 , 53 ] had a high risk of bias and seven studies [ 41 43 , 45 , 49 , 50 , 52 ] had uncertain risk of bias as there was a lack of detail in the study methodology to genuinely judge the quality of the study. Table 3 provides further details about the evidence to support judgements about risk of bias for all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…EBM knowledge and skills training constituted a component of this block. Six students were absent during the EBM labs, and 3 did not take the formative test, leaving a total study size of 71.’ Hadvani 2020 [ 35 ] Low Risk ‘We created a computer-generated randomization scheme, where each 2-week block of students were randomized to receive either TDS or SPM Low Risk The investigator (S.K.) created the scheme and was unaware of student rotation assignments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understood by those who practice it to be the "conscientious, judicious, explicit use of the current best evidence in making decisions about the care of individual patients," 1 Evidence-Based Medicine (EBM) is an important component in the education of medical professionals. Combined with other medical training, it seeks to provide a more qualitative approach to clinical care by providing more informed input for clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] A 2014 survey of US and Canadian medical schools revealed that over 100 medical schools (out of approximately 170) incorporate some form of EBM teaching in their 4-year curriculum. 9 Subsequent studies investigate both the prevalence of EBM instruction and modalities used in undergraduate medical education, 10 and found a number of different approaches, including flipped classroom settings, 1,11 online and interactive modules, hybrid courses, 12 peer-assessment seminars, 13,14 and longitudinal courses. 15 The effectiveness of such training can vary but has increased overall competence in evidence-based medicine knowledge.…”
Section: Introductionmentioning
confidence: 99%